Developing Learning Quality Through the Two Stay Two Stray Cooperative Learning Method in Increasing Student Learning Motivation - S. Fathiyatul Jannah; Qurratul Aini; Moh. Syafi’i Idrus (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2025)
This study aims to analyze the implementation of cooperative learning methods in enhancing students' learning motivation at MTs. Mambaul Hikam Soddara Pasongsungan Sumenep, as well as to determine the effectiveness of these methods. The approach taken in this research is qualitative with a case study design. The subjects of the research include Islamic Education (PAI) teachers and students of MTs. Mambaul Hikam. Data collection was conducted through interviews, observations, and documentation. This study employs a qualitative descriptive analysis method based on the ideas of Miles and Huberman. To ensure data accuracy, triangulation was performed by comparing information obtained from various sources, thereby ensuring the consistency and accuracy of the analyzed data, making the research results more trustworthy. The research findings indicate that the application of cooperative learning methods involves three stages: 1) planning, 2) implementation, and 3) evaluation. The effectiveness of this method is reflected in several indicators that have been achieved, including: 1) creating a positive classroom atmosphere, 2) enhancing students' memory retention, 3) improving verbal communication skills and self-confidence, and 4) developing students' social skills. Thus, it can be concluded that the cooperative learning method is effective in improving students' learning motivation at MTs. Mambaul Hikam.